Towards a Reduction of Grammar Teaching a Lexical Analysis - Priyono Priyono (TEFLIN, 1999)
Learning a language is essensially learning vocabulary, and it is the lexical competence that enables the learners to use the language with ease. It will be argued that such an ability includes, among the important ones, the knowledge of semantic properties and syntactic behaviour of the lexical item as well as its collocation. The acquisition of the semantic properties of a lexical item is necessary to support the learners ability to distinguish different senses encoded in the lexical item, and the knowledge of syntactic behaviour reflects the learners ability to recognize and produce the syntactic variants into which a lexical item can enter. The collocational competence is the knowledge of the lexical behaviour in particular that enables the learner to envisage the possible cooccurrence of other words with the given lexical item. Thus, the acquisition of lexical competence would cover a large part of syntax. This understanding of the nature and characteristics of lexicon would raise some questions on the relevance of putting great emphasis on the teaching of grammar only.